A new rapid molecular point-of-care assay for Trichomonas vaginalis: preliminary performance data - Pearce, David M (2013)
OBJECTIVE: Trichomonas vaginalis infection is the most prevalent treatable sexually transmitted infection (STI) in the world. An accurate point-of-care (PoC) molecular test would enable patients to be tested and treated for T vaginalis in a single visit to the genitourinary medicine clinic, community STI clinic, pharmacy or doctor’s office. In this report, we describe a rapid prototype assay for T vaginalis designed for use in conjunction with the Atlas io PoC platform, and initial verification of its performance using 90 clinical samples. METHODS: A rapid prototype T vaginalis assay was designed. The test, featuring novel electrochemical endpoint detection, used a multi-copy region of the T vaginalis genome as the assay target. Ninety clinical vaginal swab samples were used to verify the performance of the prototype assay. RESULTS: The assay demonstrated a sensitivity and specificity of 95.5% (42/44) and 95.7% (44/46), respectively, when tested using clinical samples. Assay inclusivity was demonstrated for a number of geographically diverse T vaginalis isolates, and the test showed no cross-reactivity with either human DNA or a panel of DNAs isolated from common cross-reactants. CONCLUSIONS: The sensitivity and specificity achieved using this prototype assay is comparable with that achieved for existing central laboratory nucleic acid amplification tests used for screening patients for T vaginalis.